O congado como cultura de resistência popular e educação antirracista: vozes e olhares no município de Oliveira, Minas Gerais - Paula, Alessandra Aparecida Bastos (2022)
Despite being a secular cultural celebration brought by enslaved people from different African nations and being inserted in the Brazilian cultural context, Congado still faces strong resistance of acceptance and respect from society, mainly due to religious and racial issues. The present study aims to investigate the relationship of cultural and symbolic aspects pertaining to the celebration of the celebration of N. Sra. do Rosário in the Municipality of Oliveira-MG as a foundation for the development, implementation and pedagogical actions in order to mitigate and demystify the views prejudiced in relation to this manifestation. Specifically, we intend to analyze how Congado contributed to the enrichment of pedagogical praxis anchored in the culture of resistance, in political, social, religious, corporal and racial issues in the lives of young people participating in the festivities and in the local community. The hypothesis arises in the sense of exposing that Congado presents itself as a cultural manifestation of resistance and can contribute to the expansion and creation of multidisciplinary teaching pedagogies. The subjects participating in Congado were interviewed: from its founders to young beginners. To analyze the content of the interviews and prove the scientific relevance of the study, the methodology adopted is based on the Content Analysis proposed by Laurence Bardin. The study has aspects of participatory, exploratory and descriptive research. The partial results of the study point to a difficulty in inserting the culture of Congado in pedagogical content based on ethnic-racial and cultural prejudices that still expose the wounds of more than three centuries of slavery in Brazil.